Metabolic Syndrome Risk Factors and Physical Activity in Middle-Aged Women (International Journal of Studies in Nursing, 2019)
Aim: The purpose of this study was to explore the correlation between physical activity and metabolic syndrome risk factors middle-aged women. Methods: A cross-sectional survey of 101 middle-aged women with metabolic syndrome risk factors were recruited from a regional teaching hospital in Taiwan. Surveys were conducted using a demographic questionnaire, and the Taiwanese version of the self-administered short version of the International Physical Activity Questionnaire. Results: The research results indicate that (1) 69% of the Women with metabolic syndrome were mostly in postmenopause, and the most common risk factor for metabolic syndrome was abdominal obesity (80.2%). (2) Fasting blood glucose (FBG) ≥ 100mg/dl and the level of physical activity showed significantly differences (χ2 =